Neural multimodal integration underlying synchronization with a co-performer in music: Influences of motor expertise and visual information. (16th March 2020) - Timmers, Renee; MacRitchie, Jennifer; Schabrun, Siobhan M.; Thapa, Tribikram; Varlet, Manuel; Keller, Peter E.
Highlights: IPS and dPMC are causally involved in synchronization if a co-performer is seen and heard. Cross-modal binding of visual information can decrease musical synchronization accuracy. Abstract and concrete depictions of visual movement allow action simulation for synchronization. Instrument-specific expertise improves beneficial use of visual information for synchronization. Abstract: Sensorimotor synchronization is a general skill that musicians have developed to the highest levels of performance, including synchronization in timing and articulation. This study investigated neurocognitive processes that enable such high levels of performance, specifically testing the relevance of 1) motor resonance and sharing high levels of motor expertise with the co-performer, and 2) the role of visual information in addition to auditory information. Musicians with varying levels of piano expertise (including non-pianists) performed on a single piano key with their right hand along with recordings of a pianist who performed simple melodies with the left hand, synchronizing timing and articulation. The prerecorded performances were presented as audio-only, audio-video, or audio-animation stimuli. Double pulse Transcranial Magnetic Stimulation (dTMS) was applied to test the contribution of the right dorsal premotor cortex (dPMC), an area implicated in motor resonance with observed (left-hand) actions, and the contribution of the right intraparietal sulcus (IPS), an area known for multisensory binding. Results showed effects of dTMS in the conditions that included visual information. IPS stimulation improved synchronization, although this effect was found to reverse in the video condition with higher levels of piano expertise. dPMC stimulation improved or worsened synchronization ability. Level of piano expertise was found to influence this direction in the video condition. These results indicate that high levels of relevant motor expertise are required to beneficially employ visual and motor information of a co-performer for sensorimotor synchronization, which may qualify the effects of dPMC and IPS involvement.